Hydrogen production by anaerobic digestion of crude glycerol from biodiesel fuel manufacturing process – part II. effects of biodiesel fuelrelated chemical components on hydrogen production - Yamane, Oozora (2020)
In order to utilize crude glycerol, a byproduct from biodiesel fuel production, its conversion through anaerobic fermentation was studied. Chemical components related to biodiesel fuel production were examined as substrates of anaerobic digestion. Glycerol was found to play a key role for the hydrogen production, while methanol, KOH and waste vegetable oil from which biodiesel fuel was made exerting synergetic effects.